The determinants of Nigeria's forest products trade balance - Sulaiman, Chindo; Abdul Samad, Abdul Rahim (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This paper examines the cointegration relationship between forest products trade balance and its determinants in Nigeria using the autoregressive distributed lag (ARDL) bounds testing approach. The results revealed that the variables were cointegrated. In the long run, domestic and foreign incomes have significant negative and positive impacts on the trade balance, respectively, whereas exchange rate has an insignificant impact on trade balance. In the short run, both domestic and foreign income have significant negative impacts on the trade balance. In addition, the coefficient of exchange rate also shows significant negative impact, which supports one of the assumptions of J-curve hypothesis and Marshall-Lerner condition. J-curve existence was tested, and it was revealed that it does not exist in the case of Nigeria’s trading in forest products. The results of variable decompositions and generalized impulse response tests further confirmed the earlier findings. Hence, Nigeria may have to adopt policies that are income related or growth driven to improve its forest products’ trade balance. This is because of the significant role of income variables in influencing changes in the trade balance revealed through the study.